The tale of Nicolai and the law of return / a film by David Ofek & Elinor Kowarsky. - Ofek, David, 1968-; Kowarsky, Edna; Kowarsky, Elinor (Cinephil, 2008)
With humor and irony, in a style of a tale, using an original mix genre language, the film tells the story of a Romanian worker who realizes his Jewish roots can reverse his fortune, once his Palestinian friends reveal to him the amazing advantages of a having Jewish grandmother.
Title from resource description page (viewed June 11, 2020)
Keywords: Foreign workers -- Legal status, laws, etc. -- Israel.; Foreign workers, Romanian -- Israel.; Jews -- Identity.; Jews, Romanian -- Israel.; Israel -- Emigration and immigration.; Documentary films.; Nonfiction films.